A correlational study between attitudes and oral presentation performance among undergraduates in Universiti Malaysia Pahang (UMP) - Benraghda, Abdelmadjid (2016)
The current study embarked upon the issue of English oral presentation and the students‟ attitude. It aimed to identify the students‟ attitude in delivering oral presentations and to see if there is any statistical correlation between students‟ attitude and their scores in English oral presentations. This study was conducted with 242 students in Universiti Malaysia Pahang (UMP). The most important findings indicated that students hold a positive attitude towards English oral presentations. Furthermore, the study revealed a weak positive correlation between the students‟ attitude and their scores in oral presentations in English. The qualitative approach concerns the issue of difficulties experienced by the students from delivering oral presentation. The qualitative data found six themes that are 1) Anxiety, 2) Low English proficiency, 3) Lack of support from classmates, 4) Lack of practical training, 5) Lack of teachers‟ feedback in assessing students‟ presentations and 6) pair-work presentation hinder students‟ freedom in delivering oral presentations. This study is significant as the issue of understanding the importance of the students‟ attitude will basically help teachers as well as students in developing strategies that could be fruitful to improve the students‟ English oral presentation skills.